(untitled) (European Journal of Marketing and Economics, 2018)
It is generally recognized that after the collapse of centralized economies, the private sector appears at an impressive speed in all transition economies and the number of small businesses grows by the day. It is also known that the growth of entrepreneurial activity is more oriented towards trade than industry. Albania is one of the transition countries where transition to the market economy is closely linked with the development of the private sector . A business can be created by anyone. In short we can say that a business can be created by any natural or legal person who has the capacity to act. In this category there are undoubtedly foreign and legal entities. In this regard, the main principle of Albanian law is the equality of Albanian citizens’ rights with foreign nationals except for those rights that the law recognizes only Albanian citizens. Albania has registered a rapid growth in the number of enterprises, a fact that shows a high degree of entrepreneurial desire within the country.